EVALUASI KESESUAIAN LAHAN PADI SAWAH DI DESA TANJUNG KUBAH KECAMATAN AIR PUTIH - Alridiwirsah; Mukhtar Yusuf; Hadi Wijoyo; Jhon Baker Purba (Agrica Ekstensia, 2022)
Evaluation of land suitability is very important to get agricultural crop commodities that can produce optimally. This study aims to evaluate and determine the actual and potential suitability classes as well as the efforts that can be made to improve the rice plant (Oryza sativa L.). The research was carried out from April to June 2021 at the location of 3⁰18'33.20” North Latitude and 99⁰23'2.26 East Longitude. The purpose of this research is to evaluate the suitability of the land and the improvement efforts that need to be made for the development of lowland rice plants. The analysis method uses matching data (matching field data). Determination of research location based on land map units (SPL) 1, SPL 2, SPL 3, SPL 4 and SPL 5, soil sampling was carried out at a depth of 0 to 30 cm, soil samples were analyzed in the laboratory. The results of the study found that the suitability class for lowland rice (Oryza sativa L.) was included in the appropriate class (S2) with the limiting factor for nutrient retention (nr), efforts were made to improve it by giving agricultural lime and fertilizing N, P and K so that the suitability class land can be upgraded to a potential land class (S1).